Pengelolaan Usaha dan Branding Produk Perikanan Bernilai Ekonomis di Kecamatan Pagelaran, Kabupaten Pringsewu - Helvi Yanfika; Abdul Mutolib; Begem Viantimala; Oktora Susanti (Jurnal Pengabdian Pada Masyarakat, 2021)
BUSINESS MANAGEMENT AND BRANDING OF FISHERY PRODUCTS OF ECONOMIC VALUE IN PAGELARAN SUBDISTRICT, PRINGSEWU REGENCY. Fish processors in Pagelaran District, Pringsewu, are mostly still running on simple businesses. processing fish from their parents’ tradition, so that they have ability to run a processed fish business. Processors have not been able to produce a variety of processed products, the processing group has not been able to carry out business management properly, their lack on knowledge to understand the dynamics in the group, and still low in the utilization of information technology in online marketing. Therefore, it is necessary to conduct Community Service activities (PKM) to increase the income and welfare of members of the processing group. The main problem of fish processing capacity development is because of low knowledge and skills of the community related to more modern processed technology, business management, and information technology, especially online marketing. The dedication aims to help increase the capacity of fish processing in optimizing processed fish business as a source of income. In the service will be carried out mentoring in fish processing activities with product variations, business management such as bookkeeping, and information technology. The empowerment target that will be carried out is to increase the knowledge and skills of fish processors about the quality of processed products, about business management analysis, the importance of group dynamics for the development of fish processing groups, and related to online marketing information technology is still low members of the Erwina Fish Processing Group and has not certified products.